2016
DOI: 10.1371/journal.pone.0156460
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Skeletal Muscle IL-6 Affects Pyruvate Dehydrogenase Activity at Rest and during Prolonged Exercise

Abstract: Pyruvate dehydrogenase (PDH) plays a key role in the regulation of skeletal muscle substrate utilization. IL-6 is produced in skeletal muscle during exercise in a duration dependent manner and has been reported to increase whole body fatty acid oxidation, muscle glucose uptake and decrease PDHa activity in skeletal muscle of fed mice. The aim of the present study was to examine whether muscle IL-6 contributes to exercise-induced PDH regulation in skeletal muscle. Skeletal muscle-specific IL-6 knockout (IL-6 MK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 53 publications
9
41
0
Order By: Relevance
“…While we were writing this manuscript the Pilegaard laboratory reported an RER increase in muscle-specific IL-6 KO males during 120 min of treadmill exercise [32]. They also observed a higher pyruvate dehydrogenase activity (PDH) at rest and after 60 min of exercise, and suggested that muscle IL-6 exerts an inhibitory action on skeletal muscle PDH and therefore on carbohydrate utilization, supporting the RER results.…”
Section: Discussionmentioning
confidence: 57%
“…While we were writing this manuscript the Pilegaard laboratory reported an RER increase in muscle-specific IL-6 KO males during 120 min of treadmill exercise [32]. They also observed a higher pyruvate dehydrogenase activity (PDH) at rest and after 60 min of exercise, and suggested that muscle IL-6 exerts an inhibitory action on skeletal muscle PDH and therefore on carbohydrate utilization, supporting the RER results.…”
Section: Discussionmentioning
confidence: 57%
“…Although several intracellular pathways can be activated by gp130 signaling, STAT3 activation is often regarded as the canonical pathway (13). Plasma IL-6 has been associated with muscle oxidative metabolism alterations that occur with disease and exercise (17,65). Chronically elevated plasma IL-6 in tumor-bearing mice can negatively regulate muscle mass and oxidative metabolism (3,65).…”
Section: Introductionmentioning
confidence: 99%
“…Chronically elevated plasma IL-6 in tumor-bearing mice can negatively regulate muscle mass and oxidative metabolism (3,65). Alternatively, exercise-induced increases in plasma IL-6 have been implicated in the acute metabolic response to exercise (17), and contracting muscles are a major producer of IL-6 (14,15). Although exercise can alter systemic and local intracellular signaling that regulates muscle metabolic homeostasis (11,22,48,70), our understanding of the importance of IL-6 signaling for exercise-induced mitochondrial adaptations has proven to be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, exercise training-induced increases in UCP-1 in inguinal white AT are absent in whole body IL-6 deficient mice (Knudsen et al 2014). While these findings hint at the possibility of a muscle-IL-6-AT signaling axis recent work has shown intact exercise-induced increases in circulating IL-6 from muscle specific IL-6 knockout mice (Gudiksen et al 2016) providing evidence that muscle is not the sole producer of IL-6 during exercise and/or the recovery from it.…”
Section: Catecholamines Il-6 and Other Potential Mediatorsmentioning
confidence: 96%
“…While these findings hint at the possibility of a muscle‐IL‐6‐AT signaling axis recent work has shown intact exercise‐induced increases in circulating IL‐6 from muscle specific IL‐6 knockout mice (Gudiksen et al. ) providing evidence that muscle is not the sole producer of IL‐6 during exercise and/or the recovery from it.…”
Section: Catecholamines Il‐6 and Other Potential Mediatorsmentioning
confidence: 97%